2018
DOI: 10.25073/2588-1132/vnumps.4107
|View full text |Cite
|
Sign up to set email alerts
|

Associations of single nucleotide polymorphism rs17782313 in melanocortin 4 receptor gene with anthropometric indices in normal and obesity primary school children in Hanoi

Abstract: Melanocortin-4 receptor (MC4R) has roles in regulating food intake and energy balance. A number of studies have reported that variant rs17782313 is significantly associated with obesity in many populations. However, their contribution to obesity in the Vietnamese population is not fully described. The purpose of the present study was to evaluate the association of rs17782313 with anthropometric indices and obesity in the Vietnamese children population. A case-control study was conducted on 559 children aged 6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…Our present study found the association between MC4R gene SNP rs17782313 is related to an increased level of blood pressure, total cholesterol, triglycerides, and LDL-C which is mostly similar to other studies [32, 33]. This study also found that people carrying at least one C allele were at the condition of higher BMI and at increased risk of obesity and obesity-related metabolic disorders, which is similar to many other studies [34]. A genome-wide association study which was conducted in Caucasian people found some genetic variants associated with obesity and among them, rs17782313 of MC4R was the second strongest SNP associated with higher BMI and increased risk of having obesity [35].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our present study found the association between MC4R gene SNP rs17782313 is related to an increased level of blood pressure, total cholesterol, triglycerides, and LDL-C which is mostly similar to other studies [32, 33]. This study also found that people carrying at least one C allele were at the condition of higher BMI and at increased risk of obesity and obesity-related metabolic disorders, which is similar to many other studies [34]. A genome-wide association study which was conducted in Caucasian people found some genetic variants associated with obesity and among them, rs17782313 of MC4R was the second strongest SNP associated with higher BMI and increased risk of having obesity [35].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the presence of homozygous allele CC and heterozygous allele CT was significantly associated with increased BMI, waist circumference, and hip circumference, which is similar to a Korean study that identified the variant rs17782313 was associated with higher BMI in people with minor allele C [36]. According to a case-control study by Le Thi Tuyet et al, in Vietnam, the anthropometric indices of the case group carrying the CC allele were higher than the TT allele and also the anthropometric indices were higher as compared with the control group [34]. Another study conducted on Chinese people and Tatar women also found a strong association between MC4R rs17782313 with increased BMI in subjects carrying CC and CT alleles [37,38].…”
Section: Discussionsupporting
confidence: 80%
“…Analysis of the effects of each rs6499640, rs17782313, rs6548238 SNP on obesity in primary school children in Hanoi has been reported previously. It showed that variant in the SNP rs6499640 is related to the butt circumference in normal children 8 ; SNP rs17782313 is also related to the Z-score of weight/age in normal children as well as waist-to-hip ratio in obese children 9 when SNP rs6548238 affects obesity in both recessive and cumulative genetic models 7 . This study indicated that children having 2-3 risk alleles (of the studied SNPs) has an increased the risk of obesity by nearly 1.5 times compared to those with less than 2 risk alleles (p-value=0.041).…”
Section: Discussionmentioning
confidence: 99%
“…Family characteristics, eating habits, sedentary lifestyles, and total night sleeping times were reported as the factors related to childhood obesity in primary school children in our previous reports 5,6 . Also, in primary school children in Hanoi, it was discovered that the effects of the rs6265 in BDNF (Brain derived neurotrophic factor) 6 , the rs6548238 in Transmembrane protein 18 (TMEM18) on childhood obesity 7 as well as effect of the rs6499640 in FTO (Fat mass and obesity associated) 8 , and rs17782313 in MC4R (Melanocortin 4 receptor) attributed to some anthropometric features of children 9 .…”
Section: Introductionmentioning
confidence: 99%